High IQ May "Mask" the Diagnosis of ADHD by Compensating for Deficits in Executive Functions in Treatment-Naïve Adults With ADHD. (April 2017) - Milioni, Ana Luiza Vidal; Chaim, Tiffany Moukbel; Cavallet, Mikael; de Oliveira, Nathalya Moleda; Annes, Marco; dos Santos, Bernardo; Louzã, Mario; da Silva, Maria Aparecida; Miguel, Carmen Silvia; Serpa, Mauricio Henriques; Zanetti, Marcus V.; Busatto, Geraldo; et al.
Objective: To evaluate and compare the performance of adults with ADHD with high and standard IQ in executive functions (EF) tasks.Method: We investigated the neuropsychological performance of 51 adults with ADHD, compared with 33 healthy controls (HC) while performing a wide battery of neuropsychological tests that measure executive functioning. Adults with clinical diagnosis of ADHD were divided into two groups according to their IQ level (IQ ≥ 110—ADHD group with more elevated IQ, and IQ < 110—ADHD group with standard IQ).Results: The ADHD group with standard IQ presented a worse executive functioning compared with the HC group in the following measures: Stroop 2 ( p = .000) and 3 ( p = .000), Trail Making Test (TMT) B ( p = .005), Wisconsin Card-Sorting Test (WCST)—perseverative errors ( p = .022) and failures to maintain set ( p = .020), Continuous Performance Test (CPT)—omission errors ( p = .005) and commission errors ( p = .000), and Frontal Assessment Battery (FAB)—conceptualization ( p = .016). The ADHD group with more elevated IQ presented only impairments in the CPT—commission errors ( p = .019) when compared with the control group.Conclusion: Adults with ADHD and more elevated IQ show less evidence of executive functioning deficits compared with those with ADHD and standard IQ, suggesting that a higher degree of intellectual efficiency may compensate deficits in executive functions, leading to problems in establishing a precise clinical diagnosis.